Amniotic fluid CD36 in pregnancies complicated by spontaneous preterm delivery: a retrospective cohort study - Soucek, Ondrej; Kacerovsky, Marian; Kacerovska Musilova, Ivana; Stranik, Jaroslav; Kukla, Rudolf; Bolehovska, Radka; Andrys, Ctirad (The journal of maternal-fetal & neonatal medicine, 2023)
OBJECTIVE: The aim of this study was to evaluate CD36 concentrations in amniotic fluid in pregnancies complicated by spontaneous delivery with intact fetal membranes (preterm labor, PTL) and preterm prelabor rupture of membranes (PPROM) with respect to the presence of the intra-amniotic infection. METHODS: A total of 80 women with PPROM and 71 with PTL were included in the study. Amniotic fluid samples were obtained by transabdominal amniocentesis. Amniotic fluid CD36 concentrations were assessed by enzyme-linked immunosorbent assay. Microbial colonization of the amniotic cavity (MIAC) was determined by the cultivation and non-cultivation approach. Intra-amniotic inflammation (IAI) was defined as an amniotic fluid bedside interleukin-6 concentration ≥3000 pg/mL. Intra-amniotic infection was characterized by the presence of both MIAC and IAI. RESULTS: Women with PPROM with intra-amniotic infection had higher amniotic fluid CD36 concentrations than women without infection (with infection: median 346 pg/mL, IQR 262-384 vs. without infection: median 242 pg/mL, IQR 199-304; p = .006) A positive correlation between amniotic fluid CD36 concentrations and interleukin-6 concentrations was found (rho = 0.48; p < .0001). In PTL pregnancies, no statistically significant difference was found in the amniotic fluid level of CD36 between intra-amniotic infection, sterile IAI, and negative amniotic fluid. CONCLUSIONS: The presence of intra-amniotic infection is characterized by higher amniotic fluid CD36 concentrations in pregnancies complicated by PPROM. An amniotic fluid CD36 cutoff value of 252.5 pg/mL was found to be optimal for the prediction of intra-amniotic infection. In PTL pregnancies, no statistically significant change in CD36 concentration was found with respect to the presence of intra-amniotic infection.
Keywords: intra-amniotic infection; Infant, Newborn; Retrospective Studies; retrospektivní studie; Interleukin-6; Premature Birth; Chorioamnionitis; Humans; Female; předčasný odtok plodové vody; Inflammation; novorozenec; intra-amniotic inflammation; zánět; CD36; lidé; Amniotic Fluid; ženské pohlaví; předčasný porod; interleukin-6; těhotenství; Fetal Membranes, Premature Rupture; chorioamnionitida; gestační stáří; plodová voda; Pregnancy; Gestational Age; preterm birth